Student’s thinking path in mathematics problem-solving referring to the construction of reflective abstraction - Patma Sopamena; Toto Nusantara; Eddy Bambang Irawan; Sisworo Sisworo; Kamirsyah Wahyu (Universitas Islam Negeri (UIN) Mataram, 2018)
[English]: This article is a part of research which aimed to reveal the path of undergraduate students’ thinking in solving mathematical problems referring to the construction of reflective abstraction. Reflective abstraction is the process of thinking in constructing logical structures (logico-mathematical structures) by individuals through interiorization, coordination, encapsulation, and generalization. This article seeks to analyze a student with the simple closed path, as one of the two types of students’ thinking path found in the research, in solving limit problems. The thinking process of the student in solving mathematical problems occurred through the path of interiorization - coordination - encapsulation - generalization then to coordination - encapsulation - generalization. The path of the student’s thinking yields alternative to understand and marshal problem-solving activities in mathematics learning. Keywords: Thinking path, Limit problem, Reflective abstraction, Simple closed path [Bahasa]: Artikel ini merupakan bagian dari penelitian yang bertujuan mengungkap jalur berpikir mahasiswa dalam menyelesaikan masalah matematika berdasarkan konstruksi abstraksi reflektif. Abstraksi reflektif merupakan proses berpikir individu dalam membangun struktur logika (struktur matematis logis) melalui interiorisasi, koordinasi, enkapsulasi, dan generalisasi. Artikel ini akan menganalisis seorang mahasiswa yang memiliki jalur berpikir tertutup sederhan, salah satu dari dua jalur berpikir yang terungkap dalam penelitian, dalam menyelesaikan permasalahan limit. Proses berpikir mahasiswa dalam menyelesaikan masalah matematika berdasarkan konstruksi abstraksi reflektif dapat terjadi melalui jalur interiorisasi – koordinasi – enkapsulasi – generalisasi kemudian ke koordinasi – enkapsulasi – generalisasi. Hasil penelitian ini memberikan alternatif dalam memahami dan merancang aktivitas pemecahan masalah dalam pembelajaran matematika. Kata kunci: Jalur berpikir, Masalah limit, Abstraksi reflektif, Jalur tertutup sederhana